Knockdown of TRIM35 suppresses cell proliferation and metastasis by modulating the PPAR signalling pathway in papillary thyroid cancer cells - Zhang, Liubing; Peng, Aiping; Qin, Yue (Translational Cancer Research, 2026)
Although patients with papillary thyroid cancer (PTC) generally have a favourable prognosis, they still face the possibility of recurrence after surgery. Identifying biomarkers related to PTC initiation and progression is crucial. The role and regulatory mechanisms of tripartite motif containing 35 (TRIM35) in PTC remain unclear.